Kanade, di goldene medine?: perspectives on Canadian Jewish literature and culture / perspectives sur la littérature et la culture juives canadiennes - Majer, Krzysztof; Fruzińska, Justyna; Kwaterko, Józef; Ravvin, Norman (Francopolyphonies, 2019)
"Kanade, di goldene medine: Perspectives on Canadian Jewish Literature and Culture offers a broad study of its field, with equal attention to English- and French-language materials and contexts. The volume's essays highlight the fundamental link between the culture and life of Canadian Jews and their Polish roots. This focus brings Yiddish to the fore, in essays focusing on the history of Canadian Yiddish literature, and the relevance of the language for contemporary Canadian Chasidic communities. However, essays in this volume also highlight the writings of contemporary authors, working both in French and English. Thus, the collection explores culture at the borderlands of three languages, with an eye for the link between New Worlds and Old. Kanade, di goldene medine: Perspectives sur la littérature et la culture juives canadiennes apporte une contribution importante à l'étude de la littérature et la culture juives canadiennes, tout en étant attentif aux textes et contextes anglophone et francophone ainsi qu'à l'univers particulier des juifs hassidiques de Montréal. Le volume tient également compte du lien fondamental entre la créativité des juifs canadiens et leurs racines est-européennes, en particulier polonaises, et de la présence de la langue yiddish - ou de son imaginaire - dans leurs textes sous forme de traduction ou autotraduction. Le lecteur pourra cerner dans ce livre des perspectives transversales qui mettent en relation des itinéraires multiples et diversifiés noués entre le Nouveau Monde et le Vieux" --